Considerations in the diagnosis and accelerated return to sport of a professional basketball player with a triceps surae injury: A case report - Anloague, P. A.; Strack, D. S. (Journal of Orthopaedic & Sports Physical Therapy, 2018)
Study Design: Case report. Background: Acute injuries of the triceps surae and Achilles tendon are common in sports. Rupture of the plantaris tendon can be challenging to diagnose. There is limited evidence detailing the diagnosis, rehabilitation, and accelerated return to sport of elite professional basketball players who have sustained calf injuries. Case Description: A 25-year-old male professional basketball player sustained an injury to his calf during a professional basketball game. This case report details the presumptive diagnosis, graduated progression of intervention, and return to play of a professional athlete with a likely isolated plantaris tendon tear. Outcomes: The patient returned to postseason competition 10 days post injury. Objective measures were tracked throughout rehabilitation and compared to baseline assessments. Before returning to play, the athlete showed improvements beyond the minimal clinically important difference for calf girth (2 cm) and numeric pain-rating scale score (4 points, 0-10 scale). Functional testing was conducted that included the Y Balance Test lower quarter and the Functional Movement Screen, with results that exceeded or returned the athlete to preseason levels. Discussion: This report details the case of a professional basketball player who returned to competitive play in an accelerated time frame following injury to his calf. Diagnosing a plantaris tendon rupture can be challenging, and anatomical variations of this muscle should be considered. It was demonstrated in this case that physical therapy rehabilitation was helpful in making a treatment-based clinical diagnosis when imaging was unclear. Level of Evidence: Therapy, level 5.